NOVEL CORONAVIRUS PNEUMONIA, MANAGEMENT, DIAGNOSIS AND TREATMENT- CASE REPORT - Gjorsheska, Tatjana; Kartalova, Marija Janeku (Journal of Morphological Sciences, 2021)
COVID-19 is caused by a novel coronavirus now called severe acute respiratory syndrome SARS-Cov-2. It has caused a pandemic, threatening the global public health. The most serious complication of COVID 19 is a type of pneumonia that has been called 2019 novel coronavirus pneumonia (NCIP). COVID -19 pneumonia is manifested with an atypical pneumonia and diffuse bilateral lung involvement. Severe cases present with acute lung injury and acute respiratory distress syndrome (ARDS). Potential risk factors for severe COVID-19 pneumonia include age above 65 years, diabetes, hypertension, chronic obstructive pulmonary disease, immunosuppression, HIV/AIDS, as well as other causes of immunosuppression,  sickle cell disease, malignancy, chronic kidney disease,  pregnancy, overcrowding. We present a case of our successful treatment of one COVID-19 pneumonia patient with a low mortality risk factor. The purpose is to present the clinical examination and to correlate chest X-ray with the PCR RNA test. However, we were somewhat skeptical due to negative test results (PCR RNA naso-oropharyngeal swabs were repeated three times during treatment of the infection and they remained negative and further included functional serology test .Our experience underlines the importance of the use of a multidisciplinary therapeutic approach in order to achieve a favorable clinical outcome, as well as COVID-19 diagnosis with the use of chest imaging modalities. We present a case of a 21-year-old woman with COVID-19 pneumonia, without known risk factors, who had unremarkable increase of C reactive protein and D-dimers and normal lymphocyte count during COVID-19 infection, presenting neurological symptoms as paresthesia of the lower limb. Keywords : COVID-19, SARS CoV 2; coronavirus; viral pneumonia, paresthesia (lower limb). https://doi.org/10.55302/JMS2141003gj